Efficiency Analysis of Islamic Banking in Indonesia 2015 - 2018 using Stochastic Frontier Method - Fatimah Yoshio Hata; Suharno Suharno; Muhammad Farid Alfarisy (IAIN Syekh Nurjati Cirebon, 2020)
The research objective is to analyze the efficiency of Islamic banking in Indonesia from 2015 to 2018. The quantitative approach was chosen to be used to determine and answer in this research stage. The choice of analysis in this study uses the Stochastic Frontier Approach (SFA) method. The criteria for determining variables based on estimated cost functions consist of input variables in the form of savings and labor, and output variables in the form of financing and securities, the independent variable is total costs. The sample consisted of 10 Islamic Commercial Banks (BUS) used in this study. The overall average efficiency value of Islamic banking is 85.7%, with an increase in value every year in the observation period. Savings and labor variables have a positive effect on total costs, financing variables and securities have a negative sign of total costs during the selected observation period.Keywords: efficiency, Stochastic Frontier Approach (SFA), sharia banks.